Immunotherapy of small cell lung cancer based on prognostic nutritional index - Zhang, Xinling; Zhang, Yaxuan; Zhang, Jiaqi; Yuan, Jinghua; Zhu, Shuying; Li, Xiaoping (Frontiers in Immunology, 2025)
Platinum-based first-line chemotherapy for small lung cancers has been a mainstream therapy for the past several decades. However, its efficacy has been suboptimal, and the research is now focused on improving the treatment and prognosis of competitive nutrition and multidrug combination techniques. Small cell lung cancer (SCLC) is not only affected by smoking, age, sex and other external factors, but also the tumor micro-environment and the nutritional status of patients themselves are of great significance for the prevention and treatment of SCLC, a malignant tumor. According to past research, malnutrition is related to the intolerance to immunotherapy, decline in quality of life, psychological disturbances, and low survival rates and prognosis. Numerous studies have shown that a low Prognostic Nutritional Index (PNI) serves as an independent prognostic factor linked to reduced overall survival across various cancer types. Additionally, PNI has been associated with disease-free survival and progression-free survival in certain cancers, such as lung cancer (LC). Recent research has indicated that the PNI can serve as an independent predictor of both long-term outcomes and short-term complications in SCLC patients. However, a systematic consensus on this matter has yet to be established. This paper focuses on the role and influence of PNI in the immunotherapy of SCLC, and proposes the possibility of dietary therapy for SCLC patients under the guidance of PNI. Finally, the authors pointed out that PNI will become a new strategy for comprehensive immunotherapy of SCLC.